Hubungan Jaringan Sosial Petani Sayur dengan Bauran Pemasaran Brokoli (Kasus Petani Sayur Binaan Perusda Bali di Desa Candikuning, Baturiti, Tabanan) - SUTIASIH, NI KADEK; PUTRA, I GEDE SETIAWAN ADI; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.3, Desember 2020, 2020)
The relationship between vegetable farmers’ social network and the marketing mix of broccoli (The case of vegetable farmers supervised by  Perusda Bali in Candikuning Village, Baturiti District, Tabanan) The challenges of capital, information, human resources cause farmers' products to be unable to meet market demand. Marketing of farmers' products in Perusda so far has only been to the supermarket Tiara Dewata. It can be said that the marketing network of these farmer groups is still limited. The purpose of this study was to determine the social network, marketing mix, and the relationship of social networks with the marketing mix of broccoli. Data analysis was performed with descriptive analysis through Spearman Rank Correlation and scores. This study uses qualitative and quantitative data with data collection methods through surveys, questionnaires, and interviews. The results showed that the network of power and interests are between farmers, Perusda and Tiara Dewata. The highest price mix is in the high-very high category. The lowest promotion mix is bad. The price and distribution mix is in the middle. There is a real and direct relationship between social networks with products, prices, distribution and promotion. The correlation coefficient of social networks with products and promotions is strong, social networks with prices and distribution are very strong. It can be concluded that there is a relationship between social networks and the marketing mix. It is recommended to expand distribution and promotion through ongoing cooperation.